THE AFFECT IN THE WORK OF JEAN-FRANÇOIS LYOTARD - Katwan, Ron (Surfaces, 1993)
An interpretation of the philosophical motivations that drive Jean-François Lyotard's appropriation of Freud's metapsychological concept of the affect, which, in the author's view, serves two purposes: it reinterprets first the concept of the unconscious, and second the idea of the victim.